Implicações nutricionais no tratamento e recuperação de pacientes adultos com diarréia crônica. - Dichi, I.; Papini-Berto, S. J.; Dichi, J. B.; Di Lello, A.; Victória, C. R.; Burini, Roberto Carlos [UNESP] (My University, 1991)
The nutritional assessment by 24 hour-dietary recall, anthropometry and blood-components measurements was undertaken in 23 adult patients, 17 males and 6 females suffering of chronic diarrhea from pancreatitis (30%), inflammatory bowel disease (22%), short intestine syndrome (9%) and unknown diarrhea (35%). The nutritional assessment was done at the entry and repeated at the discharge of the hospitalization that averaged 35 days, during which the patients received specific medical treatment along with obstipating diets. The hospitalization resulted in overall improvement of the patients either clinically by reducing their defecation rate or nutritionally by increasing their protein-energy intake and the values of anthropometry and blood components (albumin, free-tryptophan and lymphocytes). When the patients where divided into two groups based on their fecal-fat output one could note the better nutritional response of the group showing steatorrhea than the non-steatorrhea group, with the serum albumin and the arm-muscle circumference being discriminatory between groups. However even in the better recovered patients the indicative values of a satisfactory nutritional status were not accomplished. Thus, these data suggest that besides the overall nutritional improvement seen in the studied chronic diarrhea patients the full-nutrition recovering would demand either or both a longer hospitalization and/or an early-aggressive nutritional support.
Nutritional implications on treatment and recovery of adult patients with chronic diarrhea
Keywords: adult; caloric intake; chronic disease; comparative study; diarrhea; diet therapy; enteritis; female; human; male; nutrition; nutritional disorder; nutritional status; pancreatitis; short bowel syndrome; Adult; Chronic Disease; Comparative Study; Diarrhea; Energy Intake; English Abstract; Female; Human; Inflammatory Bowel Diseases; Male; Middle Age; Nutrition Assessment; Nutrition Disorders; Nutritional Status; Pancreatitis; Short Bowel Syndrome